Long‐Term Fluid Injection Can Expedite Fault Reactivation and Development: Riedel Shear Structures Illuminated by Induced Earthquakes in Alberta, Canada. Issue 10 (13th October 2022) - Yu, Hongyu; Kao, Honn; Wang, Bei; Visser, Ryan
Abstract: Riedel shear structures (RSS) are often observed in the embryonic stage of strike‐slip fault development, which can be depicted in the field through outcrops and coseismic surface ruptures. It is a critical concept linking the geomechanical behavior of individual earthquakes to structural geology at both local and regional scales. However, the influence of long‐term fluid injections on the developing process of RSS, as manifested by the common occurrences of injection‐induced earthquakes, has been rarely addressed. Here we document for the first‐time subsurface RSS expedited by long‐term wastewater disposal injections in western Canada. We study an earthquake sequence consisting of 187 events ( M L ranging 1.3–3.9) between 1 January 2018 and 15 July 2021 in an area without any previous seismic history. According to 31 well‐constrained focal mechanism solutions, the injection‐related earthquake sequence exhibits various faulting types with the vast majority (87%) being compatible with the background stress regime ( S Hmax azimuth = N38°E). The orientation of derived nodal planes collectively indicates a model of RSS that consists of four primary strike‐slip structures striking 19° (R′), 79° (R), 94° (PDZ), and 109° (P), respectively. Moreover, six fault segments delineated from the relocated local seismicity are parallel to the substructures of RSS. Mohr‐Coulomb failure analysis further suggests a cumulative stress perturbation of up to 10.0 MPa. Our observations suggest that long‐term fluid injection can expedite the development of local fault systems. Therefore, it is probably important to consider the dimension of local/regional RSS in the assessment of the overall seismic hazard due to fluid injections. Plain Language Summary: Under a shear stress regime, randomly distributed small fault segments would evolve into a mature strike‐slip fault system. During the early stage, a network of shear structures with favored orientations for rupturing are often observed, called Riedel shear structures (RSS). The depiction of RSS can help understand the geomechanical behavior of individual earthquakes. It is well accepted that long‐term fluid injections can cause earthquakes, yet their influence on the developing process of RSS is rarely discussed. Here we document a clear case in western Canada where the development of a local RSS system is expedited by 25 years of wastewater injection. The RSS system is manifested by an earthquake sequence consisting of 187 small‐to‐moderate‐sized events. Focal mechanisms of these events exhibit various faulting types with the majority being compatible with the background stress regime. The orientation of derived nodal planes and six fault segments depicted from the refined earthquake distribution collectively define the overall geometrical characteristics of the RSS. Mohr‐Coulomb failure analysis further suggests a cumulative stress perturbation of up to 10.0 MPa. The dimension of RSS could be important in the assessment of the overall seismic hazard due to fluid injections. Key Points: A seismically quiet area becomes active after 25 years of fluid injection Induced earthquake source characteristics indicate Riedel shear structures Long‐term fluid injection can notably expedite the reactivation and development of local fault system